Laboratory diagnosis of melioidosis: Past, present and future - Lau, Susanna KP (Exp Biol Med (Maywood), 2015)
Melioidosis is an emerging, potentially fatal disease caused by Burkholderia pseudomallei, which requires prolonged antibiotic treatment to prevent disease relapse. However, difficulties in laboratory diagnosis of melioidosis may delay treatment and affect disease outcomes. Isolation of B. pseudomallei from clinical specimens has been improved with the use of selective media. However, even with positive cultures, identification of B. pseudomallei can be difficult in clinical microbiology laboratories, especially in non-endemic areas where clinical suspicion is low. Commercial identification systems may fail to distinguish between B. pseudomallei and closely related species such as Burkholderia thailandensis. Genotypic identification of suspected isolates can be achieved by sequencing of gene targets such as groEL which offer higher discriminative power than 16S rRNA. Specific PCR-based identification of B. pseudomallei has also been developed using B. pseudomallei-specific gene targets such as Type III secretion system and Tat-domain protein. Matrix-assisted laser desorption ionization time-of-flight mass spectrometry, a revolutionary technique for pathogen identification, has been shown to be potentially useful for rapid identification of B. pseudomallei, although existing databases require optimization by adding reference spectra for B. pseudomallei. Despite these advances in bacterial identification, diagnostic problems encountered in culture-negative cases remain largely unresolved. Although various serological tests have been developed, they are generally unstandardized “in house” assays and have low sensitivities and specificities. Although specific PCR assays have been applied to direct clinical and environmental specimens, the sensitivities for diagnosis remain to be evaluated. Metabolomics is an uprising tool for studying infectious diseases and may offer a novel approach for exploring potential diagnostic biomarkers. The metabolomics profiles of B. pseudomallei culture supernatants can be potentially distinguished from those of related bacterial species including B. thailandensis. Further studies using bacterial cultures and direct patient samples are required to evaluate the potential of metabolomics for improving diagnosis of melioidosis.